2014
DOI: 10.15274/nrj-2014-10041
|View full text |Cite
|
Sign up to set email alerts
|

Lentiform Fork Sign: A Magnetic Resonance Finding in a Case of Acute Metabolic Acidosis

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…The LFS may also be present in metabolic acidosis from any cause, including end-stage renal disease, methanol intoxication, and the dialysis disequilibrium syndrome. [1][2][3][4][5][6] This study was undertaken to describe the MR imaging features in the brains of 10 patients with UE, with the aim of identifying common imaging features and potentially clarifying the possible pathophysiology of UE.…”
mentioning
confidence: 99%
“…The LFS may also be present in metabolic acidosis from any cause, including end-stage renal disease, methanol intoxication, and the dialysis disequilibrium syndrome. [1][2][3][4][5][6] This study was undertaken to describe the MR imaging features in the brains of 10 patients with UE, with the aim of identifying common imaging features and potentially clarifying the possible pathophysiology of UE.…”
mentioning
confidence: 99%
“…Cortical or subcortical areas of the brain, white matter, and basal ganglia can show abnormalities. 4,5 This sign has been reported in patients with UE, but also with dialysis disequilibrium syndrome, and also has been proposed to be associated with metabolic acidosis of any cause. 1,2 Patients with diabetes may be more predisposed because of preexisting endothelial dysfunction, making them more vulnerable to uremic toxins.…”
Section: Discussionmentioning
confidence: 83%
“…Involvement of basal ganglia is more common in Asian patients with diabetes mellitus. [5][6][7] Some authors have proposed that the lentiform fork sign is an early and reliable marker of UE and have shown it to resolve after intensive hemodialysis. Wang et al have demonstrated reduced to absent glucose metabolism in basal ganglia on F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) in patients with diabetes and uremia and basal ganglia affliction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe metabolic acidosis, with or without hypoxia and ischaemia, leads to changes in the cerebral microvascular anatomy and blood-brain barrier. These result in vasogenic oedema seen as the bright lentiform fork due to the differential metabolic vulnerability of neurons and astrocytes and may progress to cytotoxic oedema often seen as bilateral putaminal necrosis in severe cases 1. ‘Lentiform fork sign’ on MRI is a distinctive neuroradiological sign characterised by a bright hyperintense rim delineating the lentiform nucleus as a fork 2.…”
Section: Descriptionmentioning
confidence: 99%